دراسة حركة امتصاص طاقة جسيمات ألفا في بعض أبخرة المركبات العضوية النقية والمزيجة - يحيى مصطفى سليمان (Tishreen University, 2022)
دراسة حركة امتصاص طاقة جسيمات ألفا في بعض أبخرة المركبات العضوية النقية والمزيجة